Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557035
|View full text |Cite
|
Sign up to set email alerts
|

Recreating living experiences from past memories through virtual worlds for people with dementia

Abstract: This paper describes a study aimed to understand the use of 3D virtual world (VW) technology to support life engagement for people with dementia in long-term care. Three versions of VW prototypes (reminiscence room, virtual tour and gardening) utilising gestured-base interaction were developed iteratively. These prototypes were tested with older residents (80+) with dementia in care homes and their caregivers. Data collection was based on observations of how the residents and care staff interacted collaborativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 30 publications
(29 reference statements)
6
110
0
Order By: Relevance
“…A study by Siriaraya and Ang [28] conducted intriguing virtual reality mixed-method investigations ( n = 20) using different prototypes to recreating memories and social engagement in PLWD in long-term aged care. Over 9 visits, 3 different virtual reality settings (“reminiscence room,” “virtual tool,” and “gardening”) were tested in 2 aged care facilities, followed by semistructured interviews with care staff regarding the efficacy of the interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Siriaraya and Ang [28] conducted intriguing virtual reality mixed-method investigations ( n = 20) using different prototypes to recreating memories and social engagement in PLWD in long-term aged care. Over 9 visits, 3 different virtual reality settings (“reminiscence room,” “virtual tool,” and “gardening”) were tested in 2 aged care facilities, followed by semistructured interviews with care staff regarding the efficacy of the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that virtual reality activities triggered reminiscence, with participants reenacting stories from memories (i.e., their gardens). Reminiscence also occurred through their interaction with virtual objects, particularly with objects of personal relevance [28]. A sense of escapism was reported among participants, with reports of “being slipped into an alternate reality” along with positive feelings.…”
Section: Resultsmentioning
confidence: 99%
“…More recent work of the same research team [7] focused on computer-generated 3D environments providing means for people with dementia to enjoy environments they once liked, but cannot visit anymore . Similar is the work of [8], who created 3D environments for reminiscence and meaningful activities. However, people in later dementia stages had problems with the interaction.…”
Section: Current Multimedia Applications For Dementia Patientsmentioning
confidence: 76%
“…a garden or a pub. Similarly, (Siriaraya et al, 2014) utilized immersive 3D technology, in particular Unity3D and the Kinect, to create environments for reminiscence and meaningful activities (like gardening). However, people with progressed dementia had problems with the interaction.…”
Section: Technologies In Reminiscence Therapymentioning
confidence: 99%